Evaluation of Flock Volume Levels on Water Quality and Production Performance of Catfish (Clarias gariepinus) Culture Using Micropore Pipe As Aeration Diffusers. - Sumitro Sumitro; Arfan Afandi; Wa Ode Safia (Department of Aquaculture, 2022)
High floc accumulation in intensive catfish culture will increase the bacterial consumption of oxygen and affects the dissolved oxygen in the media is relatively low then affecting the fish growth. For control the floc accumulation is to remove the flock regularly. However, removing a large amount of floc will affect the flock's ability to control nitrogen waste in the water and the utilization of the flock as feed for fish will be minimum. The research was conducted to evaluate of floc volume levels on water quality and production performance of catfish culure in the biofloc system. The research design used a completely randomized design (CRD) with 4 treatments and 3 replications. The research treatments were floc volume level (KVF), namely (KVF) 20-40 ml/L, (KVF) 40-60 ml/L, (KVF) 60-80 ml/L and (KVF) 80-100 ml/L. The results showed that the water quality in all treatment were within the safe level for catfish. (KVF) 60-80 ml/L and 80-100 ml/L had higher survival rates of 100% (P <0.05). The growth rate in (KVF) 80-100 ml/L showed the lowest value compared of other treatments (P <0.05). (KVF) 60-80 ml/L can improve feed conversion ratio and increase protein retention by 59.17%, significantly different compared to other floc level treatment (P <0.05).